Framing Power and Ideology: A Critical Discourse Analysis of Elon Musk’s Town Hall Speech - Siregar, Ahmad Mulia Panigoran; Rahman, Fadhlur (ITScience (Information Technology and Science), 2025)
This study examines how language constructs power and ideology in Elon Musk’s Town Hall Speech in Pennsylvania through Fairclough’s (2010) three-dimensional model of Critical Discourse Analysis (CDA). The analysis investigates how linguistic features and rhetorical strategies function to legitimize technopopulism, a discourse that merges technocratic authority with populist appeal. Drawing on the full transcript of the speech, data were analyzed across textual, discursive, and sociocultural dimensions. The findings reveal that Musk’s discourse combines emotional populism with rational technocracy. At the textual level, metaphors, inclusive pronouns, and crisis framing generate collective urgency and moral unity. Through digital mediation on X (formerly Twitter), the speech evolves from a local communicative act into a global ideological performance. At the sociocultural level, Musk’s rhetoric naturalizes neoliberal and technocratic values such as efficiency and deregulation, framing them as moral imperatives. The study concludes that Musk’s language conceals domination behind narratives of innovation and progress, exemplifying how technopopulism legitimizes authority in digital capitalism. This research contributes to CDA scholarship by demonstrating that technological discourse not only reflects but actively shapes power relations and ideological formations in contemporary political communication.